Eksplorasi Turnover Intention Pada Generasi Z di Pontianak: Pengaruh Toxic Leadership dan Beban Kerja Melalui Stres Kerja - Riska Audina; Giriati Giriati; Pramana Saputra; Ilzar Daud; Hasanudin Hasanudin (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
Generation Z dominates the workforce in the food and beverage (F&B) sector in Pontianak City, which is known to have a high level of Turnover Intention, particularly in coffee shops and traditional cafés. This study aims to analyze the effect of Toxic Leadership and workload on Turnover Intention, with job stress as a mediating variable. A quantitative approach was employed using purposive sampling involving 150 Generation Z employees. Data were collected through questionnaires and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with SmartPLS 4.0 software. The results indicate that Toxic Leadership and workload have a positive and significant effect on job stress. Workload and job stress significantly affect Turnover Intention, while Toxic Leadership has no direct effect. Job stress is proven to significantly mediate the relationship between Toxic Leadership and workload on Turnover Intention. This study concludes that job stress plays a key role in explaining Turnover Intention among Generation Z employees. Therefore, effective workload management and the implementation of healthy leadership practices are essential to improving employee retention among Generation Z.